Gentrification and revanchist urbanism in Taipei?. (February 2016) - Jou, Sue-Ching; Clark, Eric; Chen, Hsiao-Wei
As policy and theory travel, comparative urbanism becomes important to address questions concerning if and how gentrification and revanchist urbanism have 'gone South', or 'gone East'. In recent decades, Taipei has experienced a shift in economic base, massive urban renewal, neoliberal reforms and associated social polarisation. In this paper we ask to what extent gentrification and revanchist urbanism are relevant concepts for understanding processes of urban restructuring in this East Asian developmental state capital city. The analysis relates national and urban politics to gentrification of the Yongkang, Qingtian, Wenzhou and Huaguang neighbourhoods in Daan District, Taipei. We investigate manifestations of Atkinson's four analytical strands of revanchist urbanism in Taipei. We conclude that revanchist urbanism has, to a considerable extent, formed urban development in Taipei during the last quarter century, and that unless democratising forces tame the power of finance and property capital, effectively claiming the right to the city, urban improvements by progressive movements will be valorised by the architects of revanchist urbanism: finance and property capital.